Manajemen Pengembangan Pendidik dan Tenaga Kependidikan Pada Madrasah - Hidayat Maskur; Purwanto Purwanto; Siti Choiriyah (ITB AAS INDONESIA Surakarta, 2021)
The policy for the appointment of new teachers, whether teachers in the formation of civil servants or honorary teachers, should be based on an analysis of teacher needs. The parameters for determining the needs of teachers were proposed by Cooper and Alvarado (2006: 4) based on three main components, namely pupil enrollment, pupil-teacher ratios, and turnover. The first component is that prospective students can be explained as registrants of prospective students in an educational institution, the more applicants, the more prospective students who are interested in the school are quite high. The second is the comparison between teachers and students, the presence of teachers and the number of students who must be served are the main considerations for determining the number of teacher needs. The ideal comparison between teachers and students generally uses the composition of 1 teacher serving 30 students. The research method in this research is qualitative research with direct study on the object of research. The analysis of the results shows that the needs of teachers require careful calculations regarding the calculation of needs and interests, fulfillment of rights, and others. This can be done with employee management science. Associated with the world of education, employee management is to regulate various matters relating to the management of education employees themselves. Educational personnel in a broad sense include teachers and employees or commonly referred to as Educators and Education Personnel. Edwin B. Flippo defines employee management as the management function itself, namely planning, organizing, directing, and controlling the procurement of manpower, development, compensation, integration, maintenance and termination of employment with human resources to achieve individual, organizational and community goals. . Human resource management has several functions which include planning, organizing, directing, procurement, development, compensation, integration, maintenance, discipline, and dismissal.